Phosphogypsum lightweight aggregate and preparation method thereof
By adopting the preparation method of composite core-shell structure in phosphogypsum light aggregate, the problem of low utilization rate of solid waste of phosphogypsum and steel slag is solved, resource utilization and environmental protection are achieved, and high-strength ultra-high performance concrete is prepared.
Patent Information
- Application Number
- CN202510046111.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-13
AI Technical Summary
In the prior art, the utilization rate of solid waste such as phosphogypsum and steel slag is relatively low, making it difficult to achieve resource utilization and environmental protection.
The preparation method of phosphogypsum light aggregate is adopted to prepare the core layer by using raw materials such as phosphogypsum powder, silicate cement, ore powder, water glass, sodium hydroxide, and other raw materials, and prepare the shell layer with raw materials such as steel slag powder, hollow floating beads, silicate cement, silica fume, etc. to form a composite core-shell structure for use in concrete.
It effectively improves the utilization rate of steel slag, realizes efficient absorption and resource utilization of phosphogypsum, reduces the utilization rate of sand and gravel, protects the ecological environment, and can prepare ultra-high performance concrete with a strength level of more than 100MPa.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a phosphogypsum lightweight aggregate and a preparation method thereof. Background Art
[0002] Phosphogypsum is composed of calcium sulfate dihydrate, which is grayish white or grayish black. For every ton of phosphoric acid produced, nearly 5 tons of phosphogypsum are produced. Because phosphogypsum contains soluble phosphorus, soluble fluorine, heavy metals, organic matter and trace radioactive impurities, more than 70% of phosphogypsum is difficult to be recycled. How to effectively utilize phosphogypsum solid waste has long been a technical problem that has plagued the development of the phosphorus chemical industry.
[0004] Given the current low utilization rate of solid wastes such as phosphogypsum and steel slag, it is necessary to make improvements. Summary of the invention
[0005] The present invention provides a phosphogypsum lightweight aggregate and a preparation method thereof, so as to solve or at least partially solve the defects existing in the prior art.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a phosphogypsum lightweight aggregate, comprising a core layer and a shell layer coated outside the core layer; wherein the core layer is prepared from the following raw materials in parts by weight: 55-75 parts of phosphogypsum powder, 2-7 parts of Portland cement, 5-20 parts of mineral powder, 1-3 parts of water glass, 0-2 parts of sodium hydroxide, and 13-20 parts of water;
[0008] The shell layer is prepared from the following raw materials in parts by weight: 38-58 parts of steel slag powder, 12-26 parts of hollow floating beads, 8-12 parts of silicate cement, 1-5 parts of silica fume, and 15-23 parts of water.
[0009] Preferably, the phosphogypsum comprises the following components in mass fractions:
[0010] CaO: 30.2%~43.1%, MgO: 0.47%~3.18%, Al 2 O 3 :0.57%~2.24%,SiO 2 :9.71%~16.85%, SO 3 :39.06%~48.21%,Fe 2 O 3 : 0.20%~0.66%, loss on ignition: 1.24%~2.69%;
[0011] Preferably, the steel slag powder comprises the following components in mass fractions:
[0012] CaO: 52.62% ~ 58.23%, SiO 2 :29.71%~36.85%,Al 2 O 3 : 2.57%~5.94%, MgO: 3.47%~6.68%, loss on ignition 1.72%~3.16%;
[0013] The steel slag powder has a particle size of 0.05 to 0.15 mm.
[0014] Preferably, the hollow floating beads include the following components in mass fractions:
[0015] SiO 2 :51.88%~58.34%,Al 2 O 3 :28.7%~37.12%,Fe 2 O 3 : 4.19% ~ 6.28%, MgO: 1.27% ~ 3.65%, CaO: 2.1% ~ 3.42%, SO 3 : 3.04%~5.61%;
[0016] The particle size of the hollow floating beads is 0.1 mm to 0.2 mm.
[0017] Preferably, the silicate cement is silicate cement with a strength grade of 52.5; the silica fume has a specific surface area of 20 to 30 m 2 / g; the mineral powder is S95 grade mineral powder with a specific surface area of 440-460m 2 / kg.
[0018] Preferably, the modulus of the water glass is 3.1-3.4, and the water glass is sodium water glass.
[0019] In a second aspect, the present invention further provides a method for preparing the phosphogypsum lightweight aggregate, comprising the following steps:
[0020] Adding 0 to 2 parts by weight of sodium hydroxide to 1 to 3 parts by weight of water glass to make its modulus 1.2 to 1.8, and then mixing with 13 to 20 parts by weight of water to obtain a water glass mixed solution;
[0021] Mix 55 to 75 parts by weight of phosphogypsum powder, 2 to 7 parts of Portland cement, and 5 to 20 parts of mineral powder to obtain a core layer mixture;
[0022] Mix 38 to 58 parts by weight of steel slag powder, 12 to 26 parts of hollow floating beads, 8 to 12 parts of Portland cement, and 1 to 5 parts of silica fume to obtain a shell mixture;
[0023] The core layer mixture is placed in a drum granulator, and a water glass mixed solution is added to granulate the mixture to obtain the core layer;
[0024] The core layer is placed in a disc granulator, and the shell layer mixture and 15 to 23 parts by weight of water are added to granulate to obtain a shell layer on the surface of the core layer to obtain a light aggregate;
[0025] The aggregate is placed in a carbonization kettle for carbonation curing and then subjected to standard curing to obtain phosphogypsum light aggregate.
[0026] Preferably, before mixing the phosphogypsum powder, the phosphogypsum powder is ground to obtain a specific surface area of 130 m 2 / kg of phosphogypsum;
[0027] Before mixing the steel slag powder, the steel slag powder is crushed to a particle size of ≤0.075 mm;
[0028] The particle size of the core layer is 1.18 to 2.36 mm;
[0029] The particle size of the light aggregate is 3.82-4.75 mm.
[0030] Preferably, the drum granulation mechanism has a granulation inclination angle of 45° to 65° and a rotation speed of 35 to 45 r / min;
[0031] The disc granulator mechanism has a disc inclination angle of 45° to 65° and a rotation speed of 30 to 60 r / min.
[0032] Preferably, the process parameters of carbonation curing control are: carbonization temperature is 20-25°C, relative humidity is 55%-65%, carbonization carbon dioxide pressure is 0.2-0.5MPa, and carbonization time is 8-36h;
[0033] The process parameters for standard curing control are: curing temperature of 18-22°C, relative humidity greater than or equal to 95%, and curing time of 28 days.
[0034] The phosphogypsum lightweight aggregate and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:
[0035] 1. The phosphogypsum lightweight aggregate of the present invention comprises a core layer and a shell layer coated outside the core layer, wherein the core layer is prepared from the following raw materials: phosphogypsum powder, silicate cement, mineral powder, water glass, sodium hydroxide, and water; the shell layer is prepared from the following raw materials: steel slag powder, hollow floating beads, silicate cement, silica fume, and water; the main mineral component of the steel slag powder is calcium silicate, which can react with CO 2 Carbonation reaction occurs, and f-CaO, f-MgO and Ca(OH) 2The carbonization reaction activity is high and the carbonization degree is also high. After the alkali activation effect, the hydration capacity of phosphogypsum can be improved. Steel slag and phosphogypsum are compounded into lightweight aggregate for use in concrete to construct the outer layer of CaCO 3 +CaSO lining 4 The core-shell structure can effectively improve the utilization rate of steel slag and achieve the effect of carbon fixation. At the same time, it can also achieve efficient disposal and resource utilization of phosphogypsum;
[0036] 2. The phosphogypsum light aggregate of the present invention can be applied to large-volume concrete projects, effectively reducing the utilization rate of sand and gravel and protecting the ecological environment. At the same time, the light aggregate prepared by the present invention has a cylinder pressure strength of more than 10MPa and an apparent density of 1600-1920kg / m 3 , water absorption rate 9-14%, acting on concrete, can prepare ultra-high performance concrete with strength grade of more than 100MPa, and can reduce the hydration shrinkage of concrete while maintaining a certain strength. This method used in engineering construction not only helps to solve the country's high consumption and utilization of phosphogypsum and pollution prevention and control problems, but also solves the shortage of materials needed for infrastructure construction. Compared with ordinary concrete, it has stronger market competitiveness. DETAILED DESCRIPTION
[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.
[0039] The embodiment of the present application provides a phosphogypsum lightweight aggregate, comprising a core layer and a shell layer coated outside the core layer; wherein the core layer is prepared from the following raw materials in parts by weight: 55-75 parts of phosphogypsum powder, 2-7 parts of Portland cement, 5-20 parts of mineral powder, 1-3 parts of water glass, 0-2 parts of sodium hydroxide, and 13-20 parts of water;
[0040] The shell layer is prepared from the following raw materials in parts by weight: 38-58 parts of steel slag powder, 12-26 parts of hollow floating beads, 8-12 parts of silicate cement, 1-5 parts of silica fume and 15-23 parts of water.
[0041] The phosphogypsum lightweight aggregate of the present invention comprises a core layer and a shell layer coated outside the core layer, wherein the core layer is prepared from the following raw materials: phosphogypsum powder, silicate cement, mineral powder, water glass, sodium hydroxide, and water; the shell layer is prepared from the following raw materials: steel slag powder, hollow floating beads, silicate cement, silica fume, and water; the main mineral component of the steel slag powder is calcium silicate, which can react with CO 2 Carbonation reaction occurs, and f-CaO, f-MgO and Ca(OH) 2 The carbonization reaction activity is high and the carbonization degree is also high. After the alkali activation effect, the hydration capacity of phosphogypsum can be improved. Steel slag and phosphogypsum are compounded into lightweight aggregate for use in concrete to construct the outer layer of CaCO 3 +CaSO lining 4 The core-shell structure can effectively improve the utilization rate of steel slag and achieve the effect of carbon fixation. At the same time, it can also achieve efficient disposal and resource utilization of phosphogypsum;
[0042] The phosphogypsum light aggregate of the present invention can not only efficiently dispose of solid waste phosphogypsum and realize resource utilization, but also effectively absorb and fix CO 2 . The application of the present invention in the construction industry can improve the efficiency of waste utilization, and its waste utilization rate can reach more than 50%, and the effective carbon fixation is 50% to 60%, significantly reducing carbon emissions. The composite core-shell structure of steel slag phosphogypsum is used to prepare lightweight aggregates with better performance, providing a new technical field for the large-scale utilization of various solid wastes such as phosphogypsum. It provides a theoretical and practical basis for the preparation process of phosphogypsum-based lightweight aggregates.
[0043] In some embodiments, the phosphogypsum is original phosphogypsum from Yichang City, Hubei Province, with a water content of 10-20%, a pH of 4.2, and the phosphogypsum includes the following components by mass fraction: CaO: 30.2% to 43.1%, MgO: 0.47% to 3.18%, Al 2 O 3 :0.57%~2.24%,SiO 2 :9.71%~16.85%, SO 3 :39.06%~48.21%,Fe 2 O 3: 0.20%~0.66%, loss on ignition: 1.24%~2.69%.
[0044] Before the experiment, the phosphogypsum was placed in an oven at 40°C and dried to constant weight. After grinding for 1 h, the specific surface area used in this experiment was 130 m 2 / kg of phosphogypsum.
[0045] In some embodiments, the steel slag powder is converter steel slag from Beihai City, Guangxi Zhuang Autonomous Region, and the steel slag powder includes the following components by mass fraction:
[0046] CaO: 52.62% ~ 58.23%, SiO 2 :29.71%~36.85%,Al 2 O 3 : 2.57%~5.94%, MgO: 3.47%~6.68%, loss on ignition 1.72%~3.16%;
[0047] The particle size of the steel slag powder is 0.05 to 0.15 mm.
[0048] Since the particle size of steel slag has a great correlation with the degree of carbonation reaction, steel slag needs to be ball-milled and sieved to obtain fine powder before use. The carbonization degree of steel slag with a particle size of ≤0.075mm can reach more than 85%.
[0049] In some embodiments, the hollow microspheres are floating beads from Shijiazhuang City, Hebei Province, and the hollow floating beads include the following components by mass fraction:
[0050] SiO 2 :51.88%~58.34%,Al 2 O 3 :28.7%~37.12%,Fe 2 O 3 : 4.19% ~ 6.28%, MgO: 1.27% ~ 3.65%, CaO: 2.1% ~ 3.42%, SO 3 : 3.04%~5.61%;
[0051] The bulk density of hollow floating beads is 415-420 kg / m 3 , particle size 0.1mm~0.2mm, closed and smooth surface, low thermal conductivity, refractoriness ≥1610℃.
[0052] In some embodiments, the silicate cement is a commercially available silicate cement with a strength grade of 52.5.
[0053] In some embodiments, the silica fume is commercially available silica fume with a specific surface area of 20 to 30 m 2 / g; loss on ignition ≤4.5%, water requirement ≤3.5%; containing active SiO2 Mass fraction: 93.05%.
[0054] In some embodiments, the mineral powder is S95 grade mineral powder, and the specific surface area is 440-460m 2 / kg.
[0055] In some embodiments, the modulus of the water glass is 3.1-3.4, and the water glass is sodium water glass.
[0056] In some embodiments, sodium hydroxide is commercially available in analytical grade.
[0057] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned phosphogypsum lightweight aggregate, comprising the following steps:
[0058] S1, adding 0 to 2 parts by weight of sodium hydroxide to 1 to 3 parts by weight of water glass to make its modulus 1.2 to 1.8, and then mixing with 13 to 20 parts by weight of water to obtain a water glass mixed solution;
[0059] S2, mixing 55 to 75 parts by weight of phosphogypsum powder, 2 to 7 parts of Portland cement, and 5 to 20 parts of mineral powder to obtain a core layer mixture;
[0060] S3, mixing 38 to 58 parts by weight of steel slag powder, 12 to 26 parts of hollow floating beads, 8 to 12 parts of Portland cement, and 1 to 5 parts of silica fume to obtain a shell mixture;
[0061] S4, placing the core layer mixture in a drum granulator, adding a water glass mixed solution for granulation, and obtaining a core layer;
[0062] S5, placing the core layer in a disc granulator, adding the shell layer mixture and 15 to 23 parts by weight of water, granulating, obtaining a shell layer on the surface of the core layer, and obtaining a light aggregate;
[0063] S6. Put the aggregate into a carbonization kettle for carbonation curing, and then perform standard curing to obtain phosphogypsum light aggregate.
[0064] In some embodiments, before mixing the phosphogypsum powder, the phosphogypsum powder is ground to obtain a specific surface area of 130 m 2 / kg of phosphogypsum;
[0065] Before mixing the steel slag powder, the steel slag powder is crushed to a particle size of ≤0.075 mm.
[0066] In some embodiments, the particle size of the core layer is 1.18 to 2.36 mm;
[0067] The particle size of light aggregate is 3.82~4.75mm.
[0068] In some embodiments, the drum granulation mechanism has a granulation inclination angle of 45° to 65° and a rotation speed of 35 to 45 r / min;
[0069] The disc granulator mechanism has a disc inclination angle of 45° to 65° and a rotation speed of 30 to 60 r / min.
[0070] In some embodiments, the process parameters of carbonation curing control are: carbonization temperature is 20-25° C., relative humidity is 55%-65%, carbonization carbon dioxide pressure is 0.2-0.5 MPa, and carbonization time is 8-36 h;
[0071] The process parameters for standard curing control are: curing temperature of 18-22°C, relative humidity greater than or equal to 95%, and curing time of 28 days.
[0072] Specifically, the granulated light aggregate is placed in a carbonization kettle, and after exhausting the air in the carbonization kettle, 0.2-0.5 MPa of CO is introduced. 2 The carbonization time is 8 to 36 hours. The carbonization enhancement reaction takes place. The completely carbonized lightweight aggregate needs to be placed in a standard curing room and cured in a standard manner until the corresponding age.
[0073] The phosphogypsum light aggregate of the present invention can be applied to large-volume concrete projects, effectively reducing the utilization rate of sand and gravel and protecting the ecological environment. At the same time, the light aggregate prepared by the present invention has a cylinder pressure strength of more than 10MPa and an apparent density of 1600-1920kg / m 3 , water absorption rate 9-14%, acting on concrete, can prepare ultra-high performance concrete with strength grade of more than 100MPa, and can reduce the hydration shrinkage of concrete while maintaining a certain strength. This method used in engineering construction not only helps to solve the country's high consumption and utilization of phosphogypsum and pollution prevention and control problems, but also solves the shortage of materials needed for infrastructure construction. Compared with ordinary concrete, it has stronger market competitiveness.
[0074] The following further illustrates the phosphogypsum lightweight aggregate and its preparation method of the present invention with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0075] In the following examples and comparative examples, the phosphogypsum used is the original phosphogypsum from Yichang City, Hubei Province, with a water content of 10-20%, a pH of 4.2, and the phosphogypsum includes the following components by mass fraction: CaO: 39.81%, MgO: 1.26%, Al 2 O 3 : 1.81%, SiO2 : 14.45%, SO 3 :40.56%,Fe 2 O 3 : 0.35%, loss on ignition: 1.76%.
[0076] Before the experiment, the phosphogypsum was placed in an oven at 40°C and dried to constant weight. After grinding for 1 h, the specific surface area used in this experiment was 130 m 2 / kg of phosphogypsum.
[0077] In the following examples and comparative examples, the steel slag powder used is converter steel slag from Beihai City, Guangxi Zhuang Autonomous Region, and the steel slag powder includes the following components by mass fraction: CaO: 56.62%, SiO 2 : 32.21%, Al 2 O 3 : 3.25%, MgO: 5.43%, loss on ignition 2.49%;
[0078] The average particle size of the steel slag powder is 0.1mm. The steel slag powder is crushed to a particle size of ≤0.075mm before use.
[0079] Since the particle size of steel slag has a great correlation with the degree of carbonation reaction, before using the steel slag, it needs to be ball-milled and sieved to obtain fine powder with a particle size of ≤0.075mm.
[0080] The hollow microspheres are floating beads from Shijiazhuang City, Hebei Province. The chemical composition of the hollow floating beads is:
[0081] SiO 2 : 52.68%, Al 2 O 3 : 32.26%,Fe 2 O 3 :5.19%, MgO: 2.83%, CaO: 3.12%, SO 3 : 3.92%;
[0082] The bulk density of hollow floating beads is 418.8kg / m 3 , particle size 0.1mm~0.2mm, closed and smooth surface, low thermal conductivity, refractoriness ≥1610℃.
[0083] The silicate cement is commercially available silicate cement with a strength grade of 52.5.
[0084] Silica fume is commercially available with a specific surface area of 23m 2 / g; loss on ignition ≤4.5%, water requirement ≤3.5%; containing active SiO 2 Mass fraction: 93.05%.
[0085] The mineral powder is S95 grade mineral powder with a specific surface area of about 450m 2 / kg.
[0086] The modulus of water glass is 3.3, and water glass is sodium water glass.
[0087] Example 1
[0088] The embodiment of the present application provides a phosphogypsum lightweight aggregate, comprising a core layer and a shell layer coated outside the core layer; wherein the core layer is prepared from the following raw materials in parts by weight: 69.8 parts of phosphogypsum powder, 2.1 parts of silicate cement, 8.4 parts of mineral powder, 2.2 parts of water glass, 0.48 parts of sodium hydroxide, and 17.02 parts of water;
[0089] The shell layer is prepared from the following raw materials in parts by weight: 57.2 parts of steel slag powder, 13.8 parts of hollow floating beads, 9.6 parts of silicate cement, 2.0 parts of silica fume, and 17.4 parts of water.
[0090] The method for preparing the above-mentioned phosphogypsum lightweight aggregate comprises the following steps:
[0091] S1, adding 0.48 parts by weight of sodium hydroxide to 2.2 parts by weight of water glass to make its modulus 1.5, and then mixing with 17.02 parts by weight of water to obtain a water glass mixed solution;
[0092] S2, mixing 69.8 parts by weight of phosphogypsum powder, 2.1 parts of Portland cement, and 8.4 parts of mineral powder to obtain a core layer mixture;
[0093] S3, mixing 57.2 parts by weight of steel slag powder, 13.8 parts of hollow floating beads, 9.6 parts of Portland cement, and 2.0 parts of silica fume to obtain a shell mixture;
[0094] S4, placing the core layer mixture in a drum granulator, adding the water glass mixed solution in S1 to granulate, to obtain the core layer;
[0095] S5, placing the core layer in a disc granulator, adding the shell layer mixture in S3 and 17.4 parts by weight of water, granulating, obtaining a shell layer on the surface of the core layer, and obtaining a light aggregate;
[0096] S6, placing the aggregate into a carbonization kettle, performing carbonation curing, and then performing standard curing to obtain phosphogypsum light aggregate;
[0097] The average particle size of the core layer is 1.72mm; the average particle size of the light aggregate is 3.5mm;
[0098] The drum granulation mechanism has a granulation inclination angle of 45° and a rotation speed of 35r / min;
[0099] The disc granulator mechanism has a disc inclination angle of 50° and a rotation speed of 40r / min;
[0100] The process parameters of carbonation curing control are: carbonization temperature is 25°C, relative humidity is 60%, carbonization carbon dioxide pressure is 0.4MPa, and carbonization time is 18h;
[0101] The process parameters of standard curing control are: curing temperature is 20℃, relative humidity is 96%, and curing time is 28d.
[0102] Example 2
[0103] The embodiment of the present application provides a phosphogypsum lightweight aggregate, comprising a core layer and a shell layer coated outside the core layer; wherein the core layer is prepared from the following raw materials in parts by weight: 64.3 parts of phosphogypsum powder, 4.2 parts of silicate cement, 13.8 parts of mineral powder, 1.8 parts of water glass, 0.41 parts of sodium hydroxide, and 15.49 parts of water;
[0104] The shell layer is prepared from the following raw materials in parts by weight: 49.6 parts of steel slag powder, 20.3 parts of hollow floating beads, 8.3 parts of silicate cement, 3.2 parts of silica fume, and 18.6 parts of water.
[0105] The method for preparing the above-mentioned phosphogypsum lightweight aggregate comprises the following steps:
[0106] S1, adding 0.41 parts by weight of sodium hydroxide to 1.8 parts by weight of water glass to make its modulus 1.5, and then mixing with 15.49 parts by weight of water to obtain a water glass mixed solution;
[0107] S2, mixing 64.3 parts by weight of phosphogypsum powder, 4.2 parts of Portland cement, and 13.8 parts of mineral powder to obtain a core layer mixture;
[0108] S3, mixing 49.6 parts by weight of steel slag powder, 20.3 parts by weight of hollow floating beads, 8.3 parts by weight of Portland cement, and 3.2 parts by weight of silica fume to obtain a shell mixture;
[0109] S4, placing the core layer mixture in a drum granulator, adding the water glass mixed solution in S1 to granulate, to obtain the core layer;
[0110] S5, placing the core layer in a disc granulator, adding the shell layer mixture in S3 and 18.6 parts by weight of water, granulating, obtaining a shell layer on the surface of the core layer, and obtaining a light aggregate;
[0111] S6, placing the aggregate into a carbonization kettle, performing carbonation curing, and then performing standard curing to obtain phosphogypsum light aggregate;
[0112] The average particle size of the core layer is 1.72mm; the average particle size of the light aggregate is 3.5mm;
[0113] The drum granulation mechanism has a granulation inclination angle of 45° and a rotation speed of 35r / min;
[0114] The disc granulator mechanism has a disc inclination angle of 50° and a rotation speed of 40r / min;
[0115] The process parameters of carbonation curing control are: carbonization temperature is 25°C, relative humidity is 60%, carbonization carbon dioxide pressure is 0.4MPa, and carbonization time is 18h;
[0116] The process parameters of standard curing control are: curing temperature is 20℃, relative humidity is 96%, and curing time is 28d.
[0117] Example 3
[0118] The embodiment of the present application provides a phosphogypsum lightweight aggregate, comprising a core layer and a shell layer coated outside the core layer; wherein the core layer is prepared from the following raw materials in parts by weight: 59.4 parts of phosphogypsum powder, 6.4 parts of silicate cement, 17.9 parts of mineral powder, 1.4 parts of water glass, 0.32 parts of sodium hydroxide, and 14.8 parts of water;
[0119] The shell layer is prepared from the following raw materials in parts by weight: 39.1 parts of steel slag powder, 25.5 parts of hollow floating beads, 10.4 parts of silicate cement, 3.7 parts of silica fume, and 21.3 parts of water.
[0120] The method for preparing the above-mentioned phosphogypsum lightweight aggregate comprises the following steps:
[0121] S1, adding 0.32 parts by weight of sodium hydroxide to 1.4 parts by weight of water glass to make its modulus 1.5, and then mixing with 14.8 parts by weight of water to obtain a water glass mixed solution;
[0122] S2, mixing 59.4 parts by weight of phosphogypsum powder, 6.4 parts of Portland cement, and 17.9 parts of mineral powder to obtain a core layer mixture;
[0123] S3, mixing 39.1 parts by weight of steel slag powder, 25.5 parts by weight of hollow floating beads, 10.4 parts by weight of Portland cement, and 3.7 parts by weight of silica fume to obtain a shell mixture;
[0124] S4, placing the core layer mixture in a drum granulator, adding the water glass mixed solution in S1 to granulate, to obtain the core layer;
[0125] S5, placing the core layer in a disc granulator, adding the shell layer mixture in S3 and 21.3 parts by weight of water, granulating, obtaining a shell layer on the surface of the core layer, and obtaining a light aggregate;
[0126] S6. Put the aggregate into a carbonization kettle for carbonation curing, and then perform standard curing to obtain phosphogypsum light aggregate.
[0127] The average particle size of the core layer is 1.72mm; the average particle size of the light aggregate is 3.5mm;
[0128] The drum granulation mechanism has a granulation inclination angle of 45° and a rotation speed of 35r / min;
[0129] The disc granulator mechanism has a disc inclination angle of 50° and a rotation speed of 40r / min;
[0130] The process parameters of carbonation curing control are: carbonization temperature is 25°C, relative humidity is 60%, carbonization carbon dioxide pressure is 0.4MPa, and carbonization time is 18h;
[0131] The process parameters of standard curing control are: curing temperature is 20℃, relative humidity is 96%, and curing time is 28d.
[0132] Comparative Example 1
[0133] This comparative example provides a commercially available phosphogypsum spherical aggregate with an average particle size of 3.5 mm.
[0134] Comparative Example 2
[0135] This comparative example provides a phosphogypsum lightweight aggregate, comprising the following raw materials in parts by weight: 41 parts of hemihydrate phosphogypsum, 23.2 parts of fly ash, 10.5 parts of calcined phosphate tailings, 3.3 parts of quicklime, and 22 parts of water.
[0136] The above-mentioned phosphogypsum lightweight aggregate and preparation method thereof comprise the following steps:
[0137] S1. Phosphogypsum and phosphogypsum calcined at 200°C for 2h are mixed in a mass ratio of 4:1 to obtain phosphogypsum for granulation. After phosphogypsum is calcined at 200°C for 2h, calcium sulfate dihydrate (CaSO 4 ·2H 2 O) dehydrated to obtain hemihydrate phosphogypsum (CaSO 4 0.5H 2 O), hemihydrate phosphogypsum can harden quickly, thus improving the early strength of the material;
[0138] S2, calcining the phosphate tailings at a high temperature of 1000°C for 4 hours to obtain calcined phosphate tailings; CaCO 3 MgCO 3 Decompose into CaO and MgO. The aqueous solution of CaO and MgO is alkaline, which can provide an alkaline environment for the reaction of various materials;
[0139] S3, 41 parts by weight of hemihydrate phosphogypsum, 23.2 parts by weight of fly ash, 10.5 parts by weight of calcined phosphate tailings, 3.3 parts by weight of quicklime, and 22 parts by weight of water are mixed, granulated, and naturally aged indoors for 2 hours;
[0140] S5. The granulated aggregate was moved into a constant temperature and humidity curing box for curing for 28 days (the curing temperature was 20° C. and the relative humidity was 96%) to obtain a light aggregate sample.
[0141] Performance Testing
[0142] The bulk density, apparent density, water absorption, crushing index and cylinder compression strength of the lightweight aggregate prepared in Examples 1 to 3 and Comparative Examples 1 to 2 were analyzed as shown in Table 1 below.
[0143] Table 1 - Properties of lightweight aggregates prepared in different embodiments
[0144]
[0145] It can be seen from Table 1 that the aggregate strength of the embodiments is relatively high, and the aggregate strength of embodiment 2 is relatively high at a bulk density of 900 kg / m 3 In the case of , the water absorption rate is above 10%, and the cylinder pressure strength is maintained above 10MPa. Compared with Comparative Example 1, a commercially available phosphogypsum spherical aggregate has a relatively low apparent density, but the water absorption rate and cylinder pressure strength are not high. Compared with Comparative Example 2, a phosphogypsum unburned light aggregate has a light weight, a water absorption rate of more than 20%, but a low cylinder pressure strength.
[0146] In summary, the steel slag composite phosphogypsum lightweight aggregate prepared by the present invention adopts a composite of steel slag and phosphogypsum as a core-shell structure, and the steel slag is carbonized to form CaCO 3 , which can effectively solidify phosphogypsum and increase the overall structural strength of aggregates. It can be used as lightweight aggregate to partially or completely replace sand and gravel to produce ultra-high performance concrete, with a strength grade of more than 100MPa, effectively reducing the utilization rate of sand and gravel and protecting the ecological environment. It can also be used as aggregate to produce building concrete, self-repairing concrete, road concrete, etc. Large-scale consumption of phosphogypsum and steel slag can, on the one hand, improve the utilization rate of phosphogypsum, and on the other hand, consume CO 2 It provides a new way for the comprehensive utilization of phosphogypsum and steel slag, and also provides a new idea for carbon emission reduction in the building materials industry.
[0147] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0148] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.
Claims
1. A phosphogypsum lightweight aggregate, characterized in that: It comprises a core layer and a shell layer coated outside the core layer; wherein the core layer is prepared from the following raw materials in parts by weight: 55-75 parts of phosphogypsum powder, 2-7 parts of silicate cement, 5-20 parts of mineral powder, 1-3 parts of water glass, 0-2 parts of sodium hydroxide, and 13-20 parts of water; The shell layer is prepared from the following raw materials in parts by weight: 38-58 parts of steel slag powder, 12-26 parts of hollow floating beads, 8-12 parts of silicate cement, 1-5 parts of silica fume, and 15-23 parts of water.
2. The phosphogypsum lightweight aggregate according to claim 1, characterized in that: The phosphogypsum comprises the following components by mass fraction: CaO: 30.2%~43.1%, MgO: 0.47%~3.18%, Al2O3: 0.57%~2.24%, SiO2: 9.71%~16.85%, SO3: 39.06%~48.21%, Fe2O3: 0.20%~0.66%, loss on ignition: 1.24%~2.69%.
3. The phosphogypsum lightweight aggregate according to claim 1, characterized in that: The steel slag powder includes the following components by mass fraction: CaO: 52.62% ~ 58.23%, SiO2: 29.71% ~ 36.85%, Al2O3: 2.57% ~ 5.94%, MgO: 3.47% ~ 6.68%, loss on ignition 1.72% ~ 3.16%; The steel slag powder has a particle size of 0.05 to 0.15 mm.
4. The phosphogypsum lightweight aggregate according to claim 1, characterized in that: The hollow floating beads include the following components by mass fraction: SiO2: 51.88% ~ 58.34%, Al2O3: 28.7% ~ 37.12%, Fe2O3: 4.19% ~ 6.28%, MgO: 1.27% ~ 3.65%, CaO: 2.1% ~ 3.42%, SO3: 3.04% ~ 5.61%; The particle size of the hollow floating beads is 0.1 mm to 0.2 mm.
5. The phosphogypsum lightweight aggregate according to claim 1, characterized in that: The silicate cement is silicate cement with a strength grade of 52.5; the silica fume has a specific surface area of 20 to 30 m 2 / g; the mineral powder is S95 grade mineral powder with a specific surface area of 440-460m 2 / kg.
6. The phosphogypsum lightweight aggregate according to claim 1, characterized in that: The modulus of the water glass is 3.1-3.4, and the water glass is sodium water glass.
7. A method for preparing phosphogypsum lightweight aggregate according to any one of claims 1 to 6, characterized in that: The following steps are involved: Adding 0 to 2 parts by weight of sodium hydroxide to 1 to 3 parts by weight of water glass to make its modulus 1.2 to 1.8, and then mixing with 13 to 20 parts by weight of water to obtain a water glass mixed solution; Mix 55 to 75 parts by weight of phosphogypsum powder, 2 to 7 parts of Portland cement, and 5 to 20 parts of mineral powder to obtain a core layer mixture; Mix 38 to 58 parts by weight of steel slag powder, 12 to 26 parts of hollow floating beads, 8 to 12 parts of Portland cement, and 1 to 5 parts of silica fume to obtain a shell mixture; The core layer mixture is placed in a drum granulator, and a water glass mixed solution is added to granulate the mixture to obtain the core layer; The core layer is placed in a disc granulator, and the shell layer mixture and 15 to 23 parts by weight of water are added to granulate to obtain a shell layer on the surface of the core layer to obtain a light aggregate; The aggregate is placed in a carbonization kettle for carbonation curing and then subjected to standard curing to obtain phosphogypsum light aggregate.
8. The method for preparing phosphogypsum lightweight aggregate according to claim 7, characterized in that: Before mixing the phosphogypsum powder, the phosphogypsum powder is ground to obtain a specific surface area of 130m 2 / kg of phosphogypsum; Before mixing the steel slag powder, the steel slag powder is crushed to a particle size of ≤0.075 mm; The particle size of the core layer is 1.18 to 2.36 mm; The particle size of the light aggregate is 3.82-4.75 mm.
9. The method for preparing phosphogypsum lightweight aggregate according to claim 7, characterized in that: The cylindrical granulation mechanism has a granulation inclination angle of 45° to 65° and a rotation speed of 35 to 45 r / min; The disc granulator mechanism has a disc inclination angle of 45° to 65° and a rotation speed of 30 to 60 r / min.
10. The method for preparing phosphogypsum lightweight aggregate according to claim 7, characterized in that: The process parameters of carbonation curing control are: carbonization temperature is 20-25℃, relative humidity is 55%-65%, carbonization carbon dioxide pressure is 0.2-0.5MPa, and carbonization time is 8-36h; The process parameters for standard curing control are: curing temperature of 18-22°C, relative humidity greater than or equal to 95%, and curing time of 28 days.
Citation Information
Patent Citations
Unfired artificial ardealite-based lightweight aggregate and preparation method thereof
CN115321865A
Geopolymer core-shell structure lightweight aggregate and preparation method thereof
CN116283184A
Aggregate for heat insulative concrete
JP1984003062A
Method of preparing recycled cementitious material by phosphogypsum-assisted carbon sequestration pretreatment process
US20230382790A1
Lightweight core-shell aggregate and concrete
US20240308910A1
Cited By
Phosphogypsum framework material inclusion and preparation method thereof
CN121494483A
A phosphogypsum skeleton material package and a preparation method thereof
CN121494483B